Tindak Tutur Nggahi Panati Dalam Prosesi Lamaran Pernikahan Adat Bima: Suatu Kajian Pragmatik Serta Implikasinya Dalam Pembelajaran Mulok Di Sekolah - Arifuddin, Arifuddin; Irham, Irham; Indah, Sulistia (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This pragmatic study explained three research problems, namely (1) form and meaning of nggahi panati in the marriage proposal process of Bimanese custom, (2) the significance of speech act nggahi panati in the marriage proposal process of Bimanese custom, and (3) implication of study of speech act nggahi panati in the marriage proposal process of Bimanese custom towards development of local content at schools. The data were occurrences of speech act nggahi panati in the marriage proposal process of Bimanese custom and informants. Forms of speech act nggahi panati were used in three steps, namely proposal step in form of sodi ntaru, proposal core step in form of wi’i nggahi or pita nggahi, and post-proposal step in form of wa’a co’i. The forms and meanings of speech act nggahi panati in the marriage proposal process of Bimanese custom are described through the expressions or idioms and use of patu or pantun (traditional poetry). The significance of speech act nggahi panati in the marriage proposal process of Bimanese custom has communicative functions in the forms whose categories are classified based on representative, directive, commisive, expressive, and declarative speech acts; in the cooperative principles based on maxim of quantity, quality, relevance, and manner; and in the good manner principles determined based on scales of formality, firmlessness, and friendship. Implication of analysis of speech act nggahi panati in the marriage proposal process of Bimanese custom is in the recommendation for learning of local content in local dialect in schools; which are implied in the aspects of conversation, communication, good language manner, language use, and cultural values.